ANALYSIS OF THE IMPACT OF THE DECISION OF THE CONSTITUTIONAL COURT NUMBER 2/PUU-XIX/2021 ON FIDUCIARY GUARANTEE IN BATAM - Jauza Tsania Herdin; Mohamad Fajri Mekka Putra (Sekolah Tinggi Ilmu Hukum Awang Long, 2022)
This study aims to determine and analyze the execution of fiduciary guarantees after the Constitutional Court Decision Number 2/PUU-XIX/2021 in Batam and to determine and analyze the impact of these decisions on the legal certainty of fiduciary guarantee certificates. This research is anormative-empirical research. Normative-empirical research combines library research and field research. This research is descriptive. Data was collected using literature studies and field studies. Analysis of the data used in this study is to use qualitative methods. The results showed that the execution of fiduciary guarantees after the Constitutional Court Decision Number 2/PUU-XIX/2021 in Batam was carried out in accordance with Article 29 paragraph (1) of Law Number 42 of 1999 concerning Fiduciary Guarantees. However, the determination of the debtor's breach of contract must be carried out with legal remedies, namely filing a lawsuit for default if the debtor does not provide an agreement on breach of contract and does not voluntarily submit the object of fiduciary security. The legal certainty of the fiduciary guarantee certificate of validity is reduced due to the implementation of self-execution (parate executie) by the creditor can only be carried out if the debtor agrees that he has breached his contract and submits the object of fiduciary security voluntarily.